STUDI EKSPLORASI TENTANG HARAPAN MASYARAKAT TERHADAP KEBERADAAN ASET WISATA EMBUNG TAMBAKBOYO KABUPATEN SLEMAN DAERAH ISTIMEWA YOGYAKARTA - SBS, Agus Wibowo (Sekolah Tinggi Pariwisata AMPTA, 2012)
Water Resources must be managed in a comprehensive, integrated and environmentally sound in order to realize the benefit of sustainable water resources for the prosperity of society. For the participation in explore the public’s expectations of the exsistence of an asset for tourism Embung Tambakboyo together to built awareness and anderstanding in the management of water resource in order to have aviable economic value for tsales to tourist. Three things in this effort are : I. The changing social function of the water from the objects to be object that have economic value, 2. The changing nature of the wateris Public Property inti an economic commodity that can be controlled by private owners, 3. Shifting role of goverment from provider to facilitator. From the analysis can be concluded thet based on the variables of economic, social and community participations of the three community groups (MU, PKL, KET). Increase in the economic is the main hope of street vendor and community groups have the highest expectations compared to the MU and KET. Be comprehensive to date has been the existence of Embung Tambakboyo has many positif benefits for local peoples, social and environmental sector economi and Embung Tambakboyo worthy of man-made actractions. Keywords : explorations, Community expectations, The economic value.